2008
DOI: 10.1182/blood.v112.11.224.224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Romiplostim in Patients (pts) with Low or Intermediate Risk Myelodysplastic Syndrome (MDS) Receiving Azacytidine

Abstract: Romiplostim is an investigational Fc-peptide fusion protein (peptibody) that stimulates platelet production by a mechanism similar to endogenous thrombopoietin. MDS pts receiving hypomethylating agents such as azacytidine frequently develop clinically significant thrombocytopenia. This is an ongoing phase 2 multicenter, randomized, double-blind, placebo-controlled study evaluating the effect of romiplostim on the incidence of clinically significant thrombocytopenia in pts with low or intermediate risk MDS rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Seven trials that were excluded for being in the wrong participant group (Archimbaud 1999; Geissler 2003; Han 2015; Higby 1974; Miao 2012; Moskowitz 2007; Schiffer 2000) were included in a separate review assessing alternatives, and adjuncts, to prophylactic platelet transfusion for people with haematological malignancies undergoing intensive chemotherapy or stem cell transplantation (Desborough 2016b). In total, seven studies in 25 references were deemed eligible for inclusion (Fricke 1991; Giagounidis 2014; Greenberg 2013; Kantarjian 2010; Mannucci 1986; Platzbecker 2015; Wang 2012). The four ongoing trials are expected to be reported (EudraCT 2010-022890-33; EudraCT 2014-000174-19; NCT02099747; NCT02158936).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven trials that were excluded for being in the wrong participant group (Archimbaud 1999; Geissler 2003; Han 2015; Higby 1974; Miao 2012; Moskowitz 2007; Schiffer 2000) were included in a separate review assessing alternatives, and adjuncts, to prophylactic platelet transfusion for people with haematological malignancies undergoing intensive chemotherapy or stem cell transplantation (Desborough 2016b). In total, seven studies in 25 references were deemed eligible for inclusion (Fricke 1991; Giagounidis 2014; Greenberg 2013; Kantarjian 2010; Mannucci 1986; Platzbecker 2015; Wang 2012). The four ongoing trials are expected to be reported (EudraCT 2010-022890-33; EudraCT 2014-000174-19; NCT02099747; NCT02158936).…”
Section: Resultsmentioning
confidence: 99%
“…Seven trials were published as full-text articles (published in 25 papers) between 1986 and 2015 (Fricke 1991; Giagounidis 2014; Greenberg 2013; Kantarjian 2010; Mannucci 1986; Platzbecker 2015; Wang 2012). All seven were published in English.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Kantarjian et al. reported the results of a phase 2 trial for romiplostim in patients with low‐ and intermediate‐risk MDS receiving azacytidine [35]. Interim analysis indicated that romiplostim decreased the incidence of platelet transfusions and thrombocytopenic events compared with placebo [35].…”
Section: Clinical Studies Of the Second Generation Of Tpomentioning
confidence: 99%
“…Now, at the time of publication, three drugs-azacitidine, lenalidomide, and decitabine [1][2][3] -are approved by the U.S. Food and Drug Administration (FDA) specifically for MDSrelated indications, along with at least five hematopoietic growth factors that can potentially be used for patients with MDS: epoetin, darbepoetin, filgrastim, sargramostim, and pegfilgrastim. While the thrombopoietin agonists romiplostim and eltrombopag have activity in MDS, 4,5 their use is currently restricted to patients with immune thrombocytopenia. Other active therapies used off-label for treating MDS include cytotoxic agents (such as cytarabine and clofarabine) and those with immune-modulating mechanisms of action (such as thalidomide and antithymocyte globulin).…”
Section: Department Of Hematologic Oncology and Blood Disorders Clevmentioning
confidence: 99%
“…Current and future iterations of lenalidomide-based studies are exploring combination therapy with ESAs, TPO agonists, and DNA methyltransferase inhibitors and use of the drug in higherrisk populations of MDS and AML patients. 5,39 DNA methyltransferase inhibitors themselves are being combined with a panoply of agents, ranging from growth factors and histone deacetylase inhibitors, which maximize chromatin remodeling (particularly in an Eastern Cooperative Oncology Group trial), 40 to gemtuzumab ozogamicin, in a Southwest Oncology Group trial. Most importantly, future survival studies will become de rigeur, as azacitidine has set the bar for measurement of "hard" outcomes in MDS.…”
Section: Some Other Things Newmentioning
confidence: 99%